Partisipasi Perempuan Dalam Musrenbang Perspektif Formulasi Kebijakan Inkremental - Setyawan, Dody; Ra'is, Dekki Umamur; Purwanto, Eja (Universitas Muhammadiyah Mataram, 2026)
Musyawarah Perencanaan Pembangunan (Musrenbang) is a development planning instrument that integrates top-down and bottom-up approaches, in which women’s participation is a crucial prerequisite for inclusive development planning. This study aims to analyze women’s participation in Musrenbang from a public policy formulation perspective. Employing a qualitative approach, the study was conducted in Malang City, with data collected through in-depth interviews, observation, and document analysis, and analyzed using an interactive data analysis model. The findings indicate that women’s participation in Musrenbang remains largely procedural and symbolic, limited to the stages of problem identification and agenda setting, while involvement in policy formulation remains minimal. Women’s participation is constrained by cultural and structural factors, as well as time and capacity limitations. These findings suggest that the application of an incremental policy model without affirmative mechanisms tends to reproduce participatory tokenism, thereby highlighting the need to strengthen Musrenbang through a more deliberative and gender-responsive approach.